A Cabinet in The Washing Machine. - Kim, Haeju; Lee, Sunghui; The Other Guy (Pangyo : Seodaemun-gu Recycling Center, 2012)
Kwon, Kyungwhan ; Kwon, Yongju ; Kwon, Jayeon ; Won, Dong Hwa ; Lee, Woo Sung ; Han, Sang Hyuk ; Gu, Minja ; Park, Hyungji ; Lee, Soyung ; Lee, Sunghui
A Cabinet in The Washing Machine, Seodaemun-gu Recycling Center - Pangyo Eco Center, Pangyo, 2012.6.15 - 25 ; 2012.6.29 - 9.2
boek